2022
DOI: 10.34133/2022/9807347
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Drug Delivery: Sonoporation Mechanisms, Biophysics, and Critical Factors

Abstract: Sonoporation, or the use of ultrasound in the presence of cavitation nuclei to induce plasma membrane perforation, is well considered as an emerging physical approach to facilitate the delivery of drugs and genes to living cells. Nevertheless, this emerging drug delivery paradigm has not yet reached widespread clinical use, because the efficiency of sonoporation is often deemed to be mediocre due to the lack of detailed understanding of the pertinent scientific mechanisms. Here, we summarize the current observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 198 publications
(371 reference statements)
0
45
0
Order By: Relevance
“…At low pressures, the microbubbles undergo stable cavitation, where the magnitude of their oscillating size is inversely proportional to the localized acoustic pressure and disruption to the cell membrane, whereas at high pressures, bubbles undergo inertial cavitation, resulting in large, asymmetric bubble size oscillation and the formation of penetrating liquid jets, as illustrated in Figure 3B . The efficiency of sonoporation is dependent on cellular properties as well as acoustic excitation and microbubble parameters, the understanding of which can increase efficiency and controllability of the system ( Tu and Yu, 2022 ). One such example where acoustoporation was applied to transfect pDNA encoding Cas9 and gRNA to human endometrial cancer (HEC)-1A cells is the work of Cai et al (2019) , who reported a 57% decrease of mRNA expression from the target knockout c-erbB2.…”
Section: Physical and Energetic Methods Of Deliverymentioning
confidence: 99%
“…At low pressures, the microbubbles undergo stable cavitation, where the magnitude of their oscillating size is inversely proportional to the localized acoustic pressure and disruption to the cell membrane, whereas at high pressures, bubbles undergo inertial cavitation, resulting in large, asymmetric bubble size oscillation and the formation of penetrating liquid jets, as illustrated in Figure 3B . The efficiency of sonoporation is dependent on cellular properties as well as acoustic excitation and microbubble parameters, the understanding of which can increase efficiency and controllability of the system ( Tu and Yu, 2022 ). One such example where acoustoporation was applied to transfect pDNA encoding Cas9 and gRNA to human endometrial cancer (HEC)-1A cells is the work of Cai et al (2019) , who reported a 57% decrease of mRNA expression from the target knockout c-erbB2.…”
Section: Physical and Energetic Methods Of Deliverymentioning
confidence: 99%
“…For instance, it would be worthwhile to profile the immunophenotype of sonoporated leukocytes and analyze the relevant cytokine levels to gain a deeper understanding of the post-sonoporation cytological differences between the three leukocyte subsets. Other biological factors may also be involved in influencing the level of sonoporation-induced cellular uptake and post-sonoporation viability (Shi et al 2017;Haugse et al 2020;Tu and Yu 2022). Nevertheless, not all of these previously identified biological factors are applicable to leukocytes.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…In recent years, ultrasound (US) waves have shown its great potential in clinical diagnosis and therapy 15–17 . More specific applications in thrombolysis include microbubbles (MBs) 18 or nanodroplets (NDs) 19 mediated US thrombolysis, catheter‐mediated US thrombolysis, 20–22 dual frequency US thrombolysis, 23 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultrasound (US) waves have shown its great potential in clinical diagnosis and therapy. [15][16][17] More specific applications in thrombolysis include microbubbles (MBs) 18 or nanodroplets (NDs) 19 mediated US thrombolysis, catheter-mediated US thrombolysis, [20][21][22] dual frequency US thrombolysis, 23 and so on. Among them, US thrombolysis using MBs or NDs has the merits of convenience and utility as it can be carried out well with standard products and instruments available to doctors.…”
Section: Introductionmentioning
confidence: 99%